'When you are on your own, everything is your responsibility': Experiences of audiologists and audiometrists working in rural Australia. (10th June 2021) - Kemper, Elizabeth; Willis, Karen; Simpson, Andrea
Abstract: Objective: To investigate the experiences of audiologists and audiometrists working in regional and remote areas of Australia. Design: A qualitative design, using telephone and videoconference semi‐structured interviews and thematic analysis. Setting: Regional and remote locations across Australia Participants: 5 audiologists and 2 audiometrists, 6 female and one male. Interventions: None. Main outcome measures: Insights into the experiences of audiologists and audiometrists working in rural Australia. Results: Core themes that emerged from analysis were (a) professional isolation and increased scope of practice, (b) the importance of social and professional networks, (c) variable access to professional support, (d) challenges in the recruitment and retention of clinicians, and (e) tensions between service provision and profitability. Conclusion: This study provides valuable insights into both the rewarding and challenging aspects of working as an audiologist or audiometrist in regional and remote areas. This study emphasised the need to address these challenges in order to attract more audiological professionals to work and stay in regional and remote areas of Australia.